Cerium (IV) Ammonium Nitrate (CAN) Catalyzed One-pot Synthesis of 2-Arylbenzothiazoles - Fawzia Al-Qalaf; Ramadan Ahmed Mekheimer; Kamal Usef Sadek (Molecules, 2008)
A one-pot synthesis of 2-arylbenzothiazoles from the reaction of 2-aminothiophenol and aromatic aldehydes catalysed by cerium (IV) ammonium nitrate (CAN) is reported.